2015
DOI: 10.1017/s0022215115002960
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of sudden sensorineural hearing loss in patients with depressive disorders: population-based cohort study

Abstract: The results suggest an increased risk of developing sudden sensorineural hearing loss in patients with depressive disorders. Co-morbidities such as diabetes mellitus, chronic kidney disease and hyperlipidaemia significantly aggravated the risk. Depressive disorders might be considered a risk factor for sudden sensorineural hearing loss. It remains to be seen whether control of depressive disorders can decrease the incidence of sudden sensorineural hearing loss in patients with depressive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…In accordance with the present results, several researchers have demonstrated an association between depression and SSNHL 15,16 . However, most of the previous studies focused on the incidence of depressive symptoms or depression in SSNHL patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In accordance with the present results, several researchers have demonstrated an association between depression and SSNHL 15,16 . However, most of the previous studies focused on the incidence of depressive symptoms or depression in SSNHL patients.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hands, the increased inflammation of nervous system and related comorbidities in depression patients could increase the risk of SSNHL. In line with this, one recent study reported the risk of SSNHL in depressed patients using a population-based cohort 15 . Thus, it could be inferred that the relation between depression and SSNHL might be bidirectional.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Lee et al [58] 2010, China rate of depressive symptoms especially when hearing loss is co-morbid with sexual or physical abuse, illness or additional disability, as well as feeling ostracized from family [40,48,63].…”
Section: Descriptive Survey Researchmentioning
confidence: 99%
“…Conversely, emotional factors, such as stress or depression, could induce hearing impairment [10,11]. Recently, depression was suggested to increase the risk of sudden sensorineural hearing loss with a 1.45 (95% CI = 1.12–1.86, P = 0.004) odds ratio [12]. Thus, the possible reciprocal effects between hearing impairment and depression should be considered to evaluate the impact of hearing impairment on depression.…”
Section: Introductionmentioning
confidence: 99%